THE ROLE OF DAMAR KURUNG LANTERN AS A TIME SIGNAL OF GRESIK SOCIETY - Aniendya Christianna (Jurnal Sosioteknologi, 2018)
Damar Kurung Craft is one of the typical Gresik cultural products that have been widely recorded the civilization and life of Gresik people through its handiwork. The existence of Damar Kurung has been around since the Hindu-Buddhist era. It is a lantern that made of bamboo paper with painting embedded that become Javanese's symbol of life. This research is qualitative research with descriptive approach. The object of this research is on the use of visual metaphor that described by Masmundari about Damar Kurung. The purpose of this research is to understand the meaning of symbols that embedded on Damar Kurung by Masmundari. At the same time, this writing is  made to understand the environmental context where decoration of Damar Kurung is made, in order to establish the identity and identification of Javanese people.